Dążenie do poprawy mobilności pracowniczej w Unii Europejskiej - Czaja, Jarosław (The Aspiration Towards Improving Work Mobility in EU, 2005)
The purpose of this article is to present how the European Commission pursue to increase job mobility in order to lower the unemployment level. The role of the private sector in the European job market in creating more jobs is also stressed. Unemployment and the lack of job mobility have lots of different aspects, so it is necessary to merge the efforts in reforming the European job market. The current situation of mobility is not good: in the European Union 1,2% of the population moved from one region to another in 1999, 225 000 people (0,1% of the EU population) moved between two EU countries in 2000. 16,4 % of EU workers have been with their employer for less than a year.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 396-405